Methods of evaluation of competitive activity of wrestlers with the use of computer technologies - Vyacheslav Romanenko; Valeriy Goloha; Anatoly Aleksieiev; Julia Kovalenko (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to theoretically substantiate, develop and experimentally test evaluation methods of competitive activity of combat athletes using computer technologies. Material and methods: theoretical analysis and systematization of scientific sources on the state of the research problem, generalization of modern practical experience, instrumental research method, computer programming method, methods of mathematical statistics. To carry out a research in this area Department of Martial Arts with the support of specialists of the Department of Informatics and Biomechanics developed a specialized computer program that allows to optimize the process of evaluation and analysis of competitive activity of wrestlers. Results: based on the analysis of scientific and methodological information, Internet sources and generalization of best practices, it was found that the most effective means of assessing competitive activity is video computer analysis. Also, the main parameters of competitive activity evaluation were determined. Viewing video clips of combat situations at competitions allows to identify a particular action, conditions and evaluation of its implementation more accurately. On the basis of data analysis of scientific and methodical literature and generalization of practical experience, concerning problems of an estimation and the analysis of competitive activity, the computer program "Martial Arts Video Analysis" is created. The use of the proposed computer program allows to optimize the process of analysis of competitive activities of wrestlers. The information obtained through this program will allow to form various models of competitive activity and develop guidelines for improving the quality of the training process. Conclusions: based on the analysis of scientific and methodological literature, practical experience the most significant parameters for evaluating the competitive activity of wrestlers were identified, methods with the use of computer technology that will optimize the process of evaluation and analysis of competitive activities of wrestlers was developed and tested.